Surface Transportation of the Common Habitat from Lander to Habitation Zone - Howard, Robert L.; Gomez, Jaime D.; Gill, Tracy (2023 IEEE Aerospace Conference, 2023)
The Common Habitat Architecture is a feasibility study surrounding the use of an SLS core stage liquid oxygen tank as the pressure vessel for a long-duration habitat intended for use in multiple gravity environments. The Common Habitat is used within this study as the primary habitation element in both Moon and Mars surface base camps. The Common Habitat Architecture offloads the Common Habitat from its lander and transports it to a Habitation Zone instead of leaving the habitat integrated with the lander. In this study, the Landing Zone is assumed to be approximately 3.5 kilometers from the Habitation Zone. Given the physical size and estimated 90-ton mass of the Common Habitat, a four-week trade study encompassing Moon and Mars lander identification, offloading, surface transport, and emplacement was conducted in February 2021 to assess whether there are any credible options for landing the Common Habitat on the Moon or Mars and deliver it to its intended point of use. Constrained to use only public data, the study applied subject matter expert opinion to each component of the study. The surface transportation component of the trade study assumes the habitat has been successfully offloaded from its lander and is at a point of handover to the surface transportation system. It is assumed that there are no crew present, and all human operations are performed remotely by Mission Control personnel. Three core cargo handling elements from prior NASA studies were used as the basis from which to derive surface transportation options - the Chariot, the All-Terrain Hex-Limbed Extra-Terrestrial Explorer, and the Lightweight Surface Manipulator System. Variations and hybrid combinations of these elements were used to develop transportation options for the Moon and Mars, given different habitat masses. Ultimately, several potentially feasible solutions were identified, and a solution was recommended that is common to both the Moon and Mars, with the potential to use a dissimilar system as a backup during lunar Common Habitat delivery. Next steps for sizing and additional development and analysis of the recommended surface transportation system are included as forward work.